2021
DOI: 10.1002/hep.31295
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite Motif‐Containing 27 Attenuates Liver Ischemia/Reperfusion Injury by Suppressing Transforming Growth Factor β–Activated Kinase 1 (TAK1) by TAK1 Binding Protein 2/3 Degradation

Abstract: Background and Aims Hepatic ischemia‐reperfusion (I/R) injury, which mainly involves inflammatory responses and apoptosis, is a common cause of organ dysfunction in liver transplantation (LT). As a critical mediator of inflammation and apoptosis in various cell types, the role of tripartite motif‐containing (TRIM) 27 in hepatic I/R injury remains worthy of study. Approach and Results This study systemically evaluated the putative role of TRIM27/transforming growth factor β–activated kinase 1 (TAK1)/JNK (c‐Jun … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 43 publications
1
39
0
Order By: Relevance
“…Herein, we presented two major findings. First, we found that miR-26b-5p was downregulated in the intestinal mucosa during I/R and we confirmed the protective effect I/R-induced epithelial cell apoptosis is one primary mechanism driving I/R injury [26]. Previous work has demonstrated clear roles for miRNAs in the regulation of I/R-associated epithelial cell apoptosis [27].…”
Section: Discussionsupporting
confidence: 76%
“…Herein, we presented two major findings. First, we found that miR-26b-5p was downregulated in the intestinal mucosa during I/R and we confirmed the protective effect I/R-induced epithelial cell apoptosis is one primary mechanism driving I/R injury [26]. Previous work has demonstrated clear roles for miRNAs in the regulation of I/R-associated epithelial cell apoptosis [27].…”
Section: Discussionsupporting
confidence: 76%
“…The regulation of Drp1 SUMOylation by augmenters of liver regeneration protected mitochondria from fission, rescuing hepatocytes from IRI-induced apoptosis [ 12 ]. Activating tripartite motif-containing 27 (TRIM27) prevented hepatocyte inflammation and apoptosis in hepatic IRI [ 13 ]. Hepatocyte-derived mesencephalic astrocyte-derived neurotrophic factor (MANF), an endoplasmic reticulum (ER) stress-inducible protein, alleviated hepatic IRI via regulating ER stress-induced apoptosis in mice [ 14 ].…”
Section: Acute-phase Inflammation Initiated By Hepatic Irimentioning
confidence: 99%
“…An immunohistological inspection indicated that when compared to healthy tissue, TRIM27 expression appeared higher in tissue derived from patients with Crohn disease (CD), implying that TRIM27 has a role in CD, which is a known NOD2-related inflammatory disease ( 30 ). Additionally, in a model of hepatic ischemia-reperfusion injury (IRI, which initiates from oxidative stress and inflammation caused by insufficient blood supply and subsequent reperfusion owing to trauma, resection or transplantation of the liver), TRIM27 alleviated liver damage and inflammation by suppressing the recruitment of TAK1 via TAB2/3 degradation ( 31 ). Moreover, TRIM27 interacts with multiple IKKs, including IKKα, IKKβ, IKKϵ and TBK1, to attenuate both NF-κB and IRF triggered IFN-β expression ( 32 ).…”
Section: Emerging Roles Of Mhc-i Region Encoded E3 Ubiquitin Ligases In Innate Immunitymentioning
confidence: 99%